Metabolites comparison between trunking and non-trunking sago palm (Metroxylon sage) - Yan, Wei Jei (Universiti Malaysia Sarawak(UNIMAS), 2016)
Sago palm is an important agricultural starch producing plant which contributes to the economics of Malaysia where the trunk is the main plant part that responsible for the production of the starch. However, there are sago palms that failed to develop its trunk after 17 years have been planted. This phenomenon is known as 'non-trunking' sago palm, which eliminates the economic value of the plants. Therefore, the objective of the current study was to determine metabolites that related to the non-trunking characteristics. Metabolites present in a leaf of non-trunking and trunking sago palms were extracted using the Sobolev, multiple solvent and Jones & Kinghorn extraction methods. Subsequently, the extracts were analysed using nuclear magnetic resonance spectroscopy (NMR) and gas chromatography - mass spectrometry (GC-MS). Data obtained were subjected to principal component analysis (PCA). Results showed that the Kinghorn & John extraction method was the best extraction method because it provides lower complexity NMR spectra and its PCA analysis shows the lowest significant non-correlation score of r = 0.1818 between the phenotypes. Metabolite groups which are differently express between trunking and non-trunking sago palm are oils and waxes, haloalkanes, sulfite esters, phosphonates, phosphoric acid, thiophene ester, terpenes and tocopherols. GC-MS analysis of Kinghorn & Jones extraction methods determine two sets of metabolite markers which explains the differences in metabolites expression of trunking and non-trunking sago palm in ethyl acetate and methanol extract of 89.55% comprising sulfurous ester compounds and 87.04% comprising sulfurous ester, sulfurous acid and cyclohexylmethyl hexyl ester respectively.